Selection and Validation of Reference Genes for Quantitative Real-Time PCR Normalization in Athetis dissimilis (Lepidoptera: Noctuidae) Under Different Conditions - Tang, Jinrong; Liang, Gemei; Dong, Shaoqi; Shan, Shuang; Zhao, Man; Guo, Xianru (Frontiers in Physiology, 2022)
Reference genes are the key to study gene expression patterns using quantitative real-time PCR (qRT-PCR). No studies on the reference genes of Athetis dissimilis, an important agricultural pest, have been reported. In order to determine the reference genes for qRT-PCR normalization in A. dissimilis under different conditions, 10 candidate genes [18S ribosomal protein (18S), 28S ribosomal protein (28S), arginine kinase (AK), elongation factor 1 alpha (EF1-α), glyceraldehyde-3-phosphate dehydrogenase (GAPDH), ribosomal protein L32 (RPL32), ribosomal protein L40 (RPL40), alpha-tubulin (α-TUB), beta-actin (β-ACT), and beta-tubulin (β-TUB)] of A. dissimilis were selected to evaluate their stability as reference genes under different biotic and abiotic conditions by using five tools, geNorm, NormFinder, BestKeeper, ΔCt, and RefFinder. Furthermore, CSP1 and superoxide dismutase (SOD) were used as target genes to validate the candidate reference genes. The results showed that different reference genes were needed under different experimental conditions, among which, EF-1α, RPL40, and 18S are most suitable reference genes for studying genes related development stages of A. dissimilis, RPL40 and α-TUB for larval tissues, α-TUB and 28S for adult tissues, EF-1α and β-ACT for insecticidal treatments, β-ACT and 28S for temperature treatments, EF-1α and β-ACT for starvation treatments, RPL40 and 18S for dietary treatments, and 18S, 28S, and α-TUB for all the samples. These results provide suitable reference genes for studying gene expression in A. dissimilis under different experimental conditions, and also lay the foundation for further research into the function of related genes in A. dissimilis.